1950
DOI: 10.1080/08856559.1950.10533556
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Normal and Brain-Operated Monkeys on Mechanical Puzzles with and without Food Incentive

Abstract: A. INTRODUCTION AND PROBLEMIn previous studies Harlow, Harlow, and Meyer (4) and Harlow (3) have shown that monkeys learn to solve mechanical puzzles and maintain this performance for many trials without food or any other extrinsic incentive. A manipulation drive was proposed to account for both the learning and the persistence of the behavior. In the present investigation mechanical puzzle performance is measured over a longer period of time than in previous investigations. Brain-operated as well as normal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1953
1953
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 2 publications
1
12
0
Order By: Relevance
“…Harlow and his associates (Davis, Settlage, & Harlow, 1950;Gately, 1950;Harlow, 1950Harlow, , 1953aHarlow et al, 1950) showed repeatedly that manipulating a complex mechanical puzzle made up of hasps, hooks, and hinges was intrinsically rewarding for monkeys and could be used to strengthen other responses. He posited a manipulation drive to account for these findings.…”
Section: Empirical Drive Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Harlow and his associates (Davis, Settlage, & Harlow, 1950;Gately, 1950;Harlow, 1950Harlow, , 1953aHarlow et al, 1950) showed repeatedly that manipulating a complex mechanical puzzle made up of hasps, hooks, and hinges was intrinsically rewarding for monkeys and could be used to strengthen other responses. He posited a manipulation drive to account for these findings.…”
Section: Empirical Drive Theorymentioning
confidence: 99%
“…In those studies, monkeys manipulated a mechanical puzzle apparatus, and food was introduced into the situation for some of the monkeys. In one study, Davis et al (1950) found that performance was better after this reward had been introduced and terminated than it had been before the reward was introduced. This suggests that the experience with food led the monkeys to imbue the activity with greater intrinsic value, so they were more interested in performing it well.…”
Section: Self-determination Conceptualizedmentioning
confidence: 99%
“…Specific curiosity referred to desire for a particular piece of information, while diversive curiosity referred to a general desire for perceptual or cognitive stimulation (e.g., in the case of boredom). For example, monkeys robustly exhibit specific curiosity when solving mechanical puzzles, even without food or any other extrinsic incentive (e.g., Davis, Settlage, & Harlow, 1950; Harlow, Harlow, & Meyer, 1950; Harlow, 1950). However, rats exhibit diversive curiosity when, devoid of any explicit task, they robustly prefer to explore unfamiliar sections of a maze (e.g., Dember, 1956; Hughes, 1968; Kivy, Earl, & Walker, 1956).…”
Section: Definition and Taxonomy Of Curiositymentioning
confidence: 99%
“…If decreased play effects, however, are stimulus novelty effects, repeated trials of training should weaken such effects. The available evidence consistently suggests that decreased play effects are not associated with multipletrial, contingent reinforcement procedures (e.g., Davis, Settlage, & Harlow, 1950;Feingold & Mahoney, 1975;Reiss & Sushinsky, 1975b).…”
Section: Additional Studiesmentioning
confidence: 99%